2005
DOI: 10.1071/mf04267
|View full text |Cite
|
Sign up to set email alerts
|

Why otoliths? Insights from inner ear physiology and fisheries biology

Abstract: Otoliths are of interest to investigators from several disciplines including systematics, auditory neuroscience, and fisheries. However, there is often very little sharing of information or ideas about otoliths across disciplines despite similarities in the questions raised by different groups of investigators. A major purpose of this paper is to present otolith-related questions common to all disciplines and then demonstrate that the issues are not only similar but also that more frequent interactions would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
203
0
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 269 publications
(215 citation statements)
references
References 34 publications
3
203
0
9
Order By: Relevance
“…Although otoliths (ear stones) are an important part of the auditory and vestibular sense organs in fishes (19), their formation under ocean acidification conditions has received limited attention. Previous studies of larval fish otoliths have identified consistent ocean acidification effects across some species, but have been constrained by the use of 2D measures of size, which limits further analysis of sensory consequences and the ability to examine the full extent of ocean acidification impacts (20)(21)(22).…”
mentioning
confidence: 99%
“…Although otoliths (ear stones) are an important part of the auditory and vestibular sense organs in fishes (19), their formation under ocean acidification conditions has received limited attention. Previous studies of larval fish otoliths have identified consistent ocean acidification effects across some species, but have been constrained by the use of 2D measures of size, which limits further analysis of sensory consequences and the ability to examine the full extent of ocean acidification impacts (20)(21)(22).…”
mentioning
confidence: 99%
“…Otolith merupakan organ yang berfungsi mengatur keseimbangan, pendengaran, koordinasi arah renang, dan orientasi (Bani et al, 2013;Cabello et al, 2014;Popper et al, 2005;Valinassab et al, 2012;Yilmaz et al, 2014;Sadighzadeh et al, 2014;Tuset et al, 2003). Otolith ditemukan pada semua jenis ikan kecuali hiu, pari dan lamprey (Campana, 2004).…”
Section: Pendahuluanunclassified
“…Bentuk sagittae ikan lemuru umumnya sama dengan Sardinella gibbosa, Sardinella longiceps, dan Sardinella sidensis (Homayuni et al, 2013). Kelompok ikan dari satu genus memiliki pola sulcus acusticus yang khas dan konsisten (Nolf, 1985dalam Homayuni et al, 2013, seperti halnya pada genus Sardinella ini, dimana sulcus acusticus menjelaskan kemampuan pendengaran ikan (Popper et al, 2005). Ikan yang hidup di dasar perairan memiliki rasio luas area sulcus acusticus dan sagittae secara keselururan yang lebih besar (Tuset et al, 2003).…”
Section: Karakteristik Morfologi Dan Indeks Bentuk Otolithunclassified
“…A total of 26 presentations encompassed the fundamental aspects of this theme. Popper et al (2005) provided an overview of the structure and function of otoliths, particularly with respect to hearing and balance, and how these functions change with age and growth. They also highlighted the multidisciplinary nature of otolith research and the current lack of collaborative research and information exchange among disciplines to resolve similar questions.…”
Section: Structure and Functionmentioning
confidence: 99%